2020
DOI: 10.1111/are.14590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary soy isoflavones on growth, antioxidant status, immune response and resistance of juvenile grass carp ( Ctenopharyngodon idella ) to Aeromonas hydrophila challenge

Abstract: In recent decades, due to the continuous increasing demand for aquatic products, the global fishery industry has been expanding rapidly, and aquaculture output has been increasing at an unprecedented speed (Cole et al., 2009). High-density aquaculture is the current mainstream aquaculture modes worldwide. While the environmental stress induced by high rearing density results in poor resistance to disease and vulnerability to infection by pathogenic microorganisms in fish (Costas, Aragão, Mancera, Dinis, & Conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…In present study, compared with SPC, serum AKP was remarkably increased in SI, serum GOT in dietary soy iso avone and saponin group were signi cantly increased, but serum SOD were showed the decreasing trend in dietary soy iso avone and soy saponin groups. On the one hand, dietary soy iso avone and soy saponin have antioxidant capacity for M. albus, this phenomenon was similar to juvenile grass carp (Ctenopharyngodon idella) [11] . On the other hand, these anti-nutrition factors also damaged the liver of M. albus.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…In present study, compared with SPC, serum AKP was remarkably increased in SI, serum GOT in dietary soy iso avone and saponin group were signi cantly increased, but serum SOD were showed the decreasing trend in dietary soy iso avone and soy saponin groups. On the one hand, dietary soy iso avone and soy saponin have antioxidant capacity for M. albus, this phenomenon was similar to juvenile grass carp (Ctenopharyngodon idella) [11] . On the other hand, these anti-nutrition factors also damaged the liver of M. albus.…”
Section: Discussionmentioning
confidence: 75%
“…A paper also reported that dietary soy saponin made higher expression of intestinal IL-1β and IL-8 on juvenile turbot (Scophthalmus maximus), and damaged the intestinal barrier and induced enteritis [6] . While dietary soy iso avone improved immune performance (such as the responses of immune cytokines) of juvenile grass carps [11] . We think that herbivorous sh may have higher adaptability to plant anti-nutritional factors than carnivorous sh.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations